Tree Planting Program for Disaster Mitigation in South Pringgasela Village, Pringgasela District, East Lombok Regency - Aldy Ramadhan; Yulia Azmi Khotimah; Sindi Hikmala; Rina Sasmita Alfani; Muliadi; Muhammad Marwin; M. Teguh Jaka Satya Samudra Jati Suara; Indah Nahdiat Isrori; Dini Rosyida; Desti Suci Safitri; Chalida Alfany; Akbar Prayoga; Syamsuddin Syamsuddin (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
South Pringgasela Village, located in Pringgasela District, East Lombok Regency, is one of the areas at risk of natural disasters such as landslides and floods. To support reforestation and disaster mitigation, community service activities have been carried out by students of the 2021-2022 Mataram University Community Service Program (KKN). This activity focuses on planting trees on empty land and road cliffs around the Pancor Kopong tourist area, including the Goa Kopong spring tourist location. Tree planting is carried out to increase soil resistance to erosion and create a greener environment. The process of implementing the activity involved coordination with various parties, including village officials, mosque youth, and the local community. A total of 150 tree seedlings were successfully planted, with a growth success rate of 86% based on post-activity evaluations. The results of this activity show a positive impact on the environment, such as increasing the aesthetics of the tourist area, reducing disaster risks, and increasing public awareness of the importance of environmental conservation. This reforestation activity is expected to be the first step to encourage active community participation in protecting the environment and become a model for implementing conservation-based community service. Furthermore, the success of this program can be an inspiration for other regions in implementing disaster mitigation strategies through reforestation.